Inhibitory modulation of age-dependent behavior through dsx -expressing cells in honeybees - Jana Seiler; Pia Ulbricht; Vivien Sommer; Sabine Metzger; Bernd Grünewald; Martin Beye (Proceedings of the National Academy of Sciences, 2026)
Social insects exhibit distinct age-dependent behavioral repertoires that collectively contribute to the common benefits of a colony. However, how the nervous system manifests the capacity of such age-dependent, disparate behavioral repertoires underlying the division of labor is largely unknown. In honeybee ( Apis mellifera ), a classical model of such age-dependent polyethism, young but not older worker bees attend and feed the queen (retinue behavior), which is triggered by the queen mandibular pheromone (QMP). Here, we revealed that older bees are still equipped with a latent QMP retinue response that is, however, modulated by the electrical activity of doublesex -expressing ( dsx + ) cells. We genetically expressed a designed neuron silencer hM4Di protein from the endogenous dsx promoter. We conditionally activated this receptor protein by feeding or not feeding the synthetic ligand C21. Eight- to 11-day-old worker bees displayed a retinue-like QMP response under electrical silencing conditions (+C21) but not under nonsilencing conditions (−C21). Control experiments demonstrated that the administration of the ligand C21 could not account for the observed increase in retinue behaviors in older bees, which is otherwise only observed in younger bees. Our study suggests an inhibitory role of dsx + cells of age-dependent retinue behaviors and establishes an unexplored connection between polyethism and its manifestation in the nervous system. Hence, chemogenetically driven manipulations suggest inroads for examining the division of labor at the level of neuronal activity.